Artisanal and Small-Scale Gold Mining : A Framework for Collecting Site-Specific Sampling and Survey Data to Support Health-Impact Analyses - World Bank (World Bank, Washington, DC, 2021)
Artisanal gold mining occurs informally and therefore relies on low technologies and extraction methods lacking pollution controls. As a result, despite the fact that artisanal gold mining produces only twenty percent of the world’s gold, it releases more mercury than any other sector and represents the largest source of mercury emissions. At various points during the gold mining process, mercury is released and emitted into the atmosphere during various points in the gold mining process, where it deposits into soil, lakes, and rivers. This framework document provides a pragmatic approach for designing representative studies and developing uniform sampling guidelines to support estimates of morbidity that are explicitly linked to exposure to land-based contaminants from small-scale artisanal gold mining activities. A primary goal is to support environmental burden of disease evaluations, which attempt to attribute health outcomes to specific sources of pollution. The guidelines provide recommendations on the most appropriate and cost-effective sampling and analysis methods to ensure the collection of representative population-level data, sample-size recommendations for each contaminant and environmental media, biological sampling data, household-survey data, and health-outcome data. Section 1 of the guidelines provides an overview of the Artisanal and Small-Scale Gold Mining (ASGM) process, including a description of the primary contaminants released or discharged during each step of the process. Section 2 describes the process for identifying participating households and individuals within those households that will provide household survey data, environmental sampling data, biomonitoring data, and health-outcomes data. Section 3 provides general guidelines for conducting environmental sampling of soil, dust, sediment, water, fish, and/or agricultural and food products. Section 4 provides general guidelines for collecting biomonitoring samples in blood, urine, hair, or other biological matrices. Section 5 provides general guidelines for evaluating health outcomes using medical exams, health surveys, and diagnostic tests.